Control financiero de la empresa Implanet S. A. de la ciudad de Guayaquil. - Castro Peña, Yosdy Yulen (2022)
The present investigation is based on the financial control of the company Implanet S.A belonging to the city of Guayaquil; institution dedicated to providing Internet contracting services in provinces such as Guayas and Los Ríos. As its name indicates, the general objective of this case is to analyze the accounting books where the true situation of the entity is reflected during the 2020-2021 pandemic period, and the influence of income and expenses on the strategic planning of the present accounting exercise. The methodology applied in this case study is deductive, starting from the general conclusions detected in the organization on financial control, until understanding the particular premises that pose the accounting situations that put the economic stability of the company Implanet S.A. at risk. The research is of a descriptive-bibliographic nature, through the description of the information found thanks to the instruments and techniques carried out for the collection of data in the institution (questionnaires, observation, surveys and interviews) it is intended to expose with valid theoretical foundations. sources, the influence of income, expenses among other economic factors found in the entity's decision making.